Answer:
Simplifying
7 + -1(4p + 3) = -3(p + 2) + -1(2P + 3)
Reorder the terms:
7 + -1(3 + 4p) = -3(p + 2) + -1(2P + 3)
7 + (3 * -1 + 4p * -1) = -3(p + 2) + -1(2P + 3)
7 + (-3 + -4p) = -3(p + 2) + -1(2P + 3)
Combine like terms: 7 + -3 = 4
4 + -4p = -3(p + 2) + -1(2P + 3)
Reorder the terms:
4 + -4p = -3(2 + p) + -1(2P + 3)
4 + -4p = (2 * -3 + p * -3) + -1(2P + 3)
4 + -4p = (-6 + -3p) + -1(2P + 3)
Reorder the terms:
4 + -4p = -6 + -3p + -1(3 + 2P)
4 + -4p = -6 + -3p + (3 * -1 + 2P * -1)
4 + -4p = -6 + -3p + (-3 + -2P)
Reorder the terms:
4 + -4p = -6 + -3 + -2P + -3p
Combine like terms: -6 + -3 = -9
4 + -4p = -9 + -2P + -3p
Solving
4 + -4p = -9 + -2P + -3p
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '3p' to each side of the equation.
4 + -4p + 3p = -9 + -2P + -3p + 3p
Combine like terms: -4p + 3p = -1p
4 + -1p = -9 + -2P + -3p + 3p
Combine like terms: -3p + 3p = 0
4 + -1p = -9 + -2P + 0
4 + -1p = -9 + -2P
Add '-4' to each side of the equation.
4 + -4 + -1p = -9 + -4 + -2P
Combine like terms: 4 + -4 = 0
0 + -1p = -9 + -4 + -2P
-1p = -9 + -4 + -2P
Combine like terms: -9 + -4 = -13
-1p = -13 + -2P
Divide each side by '-1'.
p = 13 + 2P
Simplifying
p = 13 + 2P
Explanation: